The right to roam: a review of policy and management of public access to land - Hughes, Michael; Tye, M.; Zulfa, Mariyam (WA Department of Sport and Recreation, 2010)
This report presents an international review of policy and management regarding public recreational access to land of varying tenure. This is an increasingly important issue in Australia with a growing population and the associated pressure on natural resources to provide a range of services and needs. Reviewing policy and management in regions where recreation access rights have been established across tenures will inform a strategic research direction for managing public recreational access to land in WA. The report is based on a desktop exercise and collaboration with WA Government representatives to source information relating to recreational access to land legislation in the UK, New Zealand and Western Australia. Information was sourced from published material, official websites and personal communications. The objectives were to: review the various elements that form the current legislative context for recreational access in UK and New Zealand; identify the various elements that form the current context in WA for outdoor recreational access; and develop a summary of implications resulting from comparisons of the WA, UK and NZ contexts.